Risk Management Analysis of Banana Chips Sellers in Pematang Johar Village - Harahap, Nur Anzelina; Hardianto, Hardianto; Tambunan, Frinto; Lutfiyani , Nila; Samosir , Santha Yosephine G (Gayaku Publisher, 2022)
Risk will always be faced by anyone, including business people because to unpredictable uncertainties that can cause losses in the business. So are small and medium enterprises that have a less strong capital background. Where many of the sellers do not understand and know risk management, therefore, this study aims to analyze the risk management of selling banana chips in the village of Pematang Johar, to find out whether the sellers of banana chips in the village of Pematang Johar understand management risks in selling banana chips. The purpose of this research is to find out how many banana chip sellers in Pematang Johar village do not understand management risk. The method used is field research that collects data by direct observation or observation. Risk management itself is a risk management process that includes support, evaluation, and control of risks that can threaten the continuity of a company's business or activities. One of the objectives of risk management is to reduce expenses, prevent companies from failing, increase company profits, and reduce production costs for making chips banana.